2014
DOI: 10.3168/jds.2013-7822
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rearing substrate and space allowance on the behavior and physiology of dairy calves

Abstract: The objective of this study was to investigate the effect of rearing substrate and space allowance on the behavior and physiology of dairy calves. At 1 wk of age, 72 calves were moved into 1 of 18 experimental pens (n=4 calves/pen) where they remained until 6 wk of age. Half of the pens had floors covered with quarry stones (QS) and the other half were covered with sawdust (SW). For each substrate type, calves were reared at 1 of 3 space allowances: 1.0, 1.5, or 2.0 m(2)/calf. Behavior was video-recorded conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Terre et al (2006a) observed no difference in serum cortisol concentration of calves that were individually or group housed and fed an enhanced milk replacer feeding regimen. Likewise, Sutherland et al (2014) observed no differences in serum cortisol in calves up to 6 wk of age with different bedding types or space allocations. In 7-mo-old beef heifers, Hickey et al (2003) either weaned calves abruptly weaned or did not wean and blood samples were taken beginning 168 h before weaning and at 24, 48, and 168 h after weaning.…”
Section: Discussionmentioning
confidence: 72%
“…Terre et al (2006a) observed no difference in serum cortisol concentration of calves that were individually or group housed and fed an enhanced milk replacer feeding regimen. Likewise, Sutherland et al (2014) observed no differences in serum cortisol in calves up to 6 wk of age with different bedding types or space allocations. In 7-mo-old beef heifers, Hickey et al (2003) either weaned calves abruptly weaned or did not wean and blood samples were taken beginning 168 h before weaning and at 24, 48, and 168 h after weaning.…”
Section: Discussionmentioning
confidence: 72%
“…Daily feeding patterns differed over the hours of the day (P < 0.001, Figure 4), with peaks in standing activity corresponding to the delivery of milk (0600 h and 1800 h) in wk 1 ( Figure 4A), and arrival of farm staff and external cues of other calves receiving milk in wk 8 (postweaning, Figure 4B). In general, lying time in young calves is encouraged through management factors, such as softer bedding (Sutherland et al, 2014), and is considered an indicator of comfort. Further, Hänninen et al (2005) described a positive correlation between lying time and ADG in preweaned calves, suggesting that adequate rest is important for calf performance.…”
Section: Activity Patterns and Behavior During Early Life And Weaningmentioning
confidence: 99%
“…In addition to the in utero effects, recent studies have shown that heat stress also exerts carryover effects on the postnatal performance of the offspring during the preweaning period, including immune function (Tao et al, 2012a;Monteiro et al, 2014;Strong et al, 2015) and metabolic adaptations (Tao et al, 2014;Monteiro et al, 2016b). Understanding behavior is also a valuable tool when assessing animal welfare, and activity patterns are influenced by a range of factors, such as bedding material and comfort (Sutherland et al, 2014), and health (Proudfoot et al, 2014). Activity is also influenced by temperature: both calves and cows spend less time lying down in hot summer temperatures (Overton et al, 2002;Tripon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dairy calves also show a clear preference for lying on dry WS and an aversion to lying on bare concrete (Camiloti et al, 2012) and prefer lying on WS than on SA (Worth et al, 2015). However, some organic substrates are becoming difficult or expensive for farmers to obtain, have higher moisture absorbent properties, and have higher bacteria contamination (Panivivat et al, 2004;Sutherland et al, 2014b). Therefore, rearing substrates that are easily accessible and that maintain good calf health and welfare need evaluating.…”
Section: Introductionmentioning
confidence: 99%